Epidemiological serosurvey of chikungunya fever post outbreak at Tanjung Sepat, Malaysia - Khor, Chee-Sieng; Teoh, Boon-Teong; Sam, Sing-Sin; Khoo, Hooi-Yuen; Azizan, Noor-Syahida; CheMatSeri, AsmaAnati; Chin, Kim-Ling; Hamim, Zur-Raiha; Mohamed-Romai-Noor, Noor-Adila; Yaacob, Che-Norainon; Abd-Jamil, Juraina; Lee, Hai-Yen; et al. (The Journal of Infection in Developing Countries, 2023)
Introduction: Chikungunya fever is a mosquito-borne viral disease that usually presents with prominent arthralgia. An outbreak of chikungunya fever was reported in Tanjung Sepat, Malaysia in 2019. The outbreak was limited in size with a low number of cases being reported. The present study sought to determine the possible variables that could have affected the transmission of the infection. Methodology: A cross-sectional study involving 149 healthy adult volunteers from Tanjung Sepat was performed soon after the outbreak had subsided. All the participants donated blood samples and completed the questionnaires. Laboratory detection of anti-CHIKV IgM and IgG antibodies was performed using enzyme-linked immunoassays (ELISA). Risk factors associated with chikungunya seropositivity were determined using logistic regression. Results: The majority (72.5%, n = 108) of the study participants tested positive for CHIKV antibodies. Only 8.3% (n = 9) of the participants out of all the seropositive volunteers had an asymptomatic infection. Participants who resided with a febrile (p < 0.05, Exp(B) = 2.2, confidence interval [CI] 1.3-3.6) or a CHIKV-diagnosed person (p < 0.05, Exp(B) = 2.1, CI 1.2-3.6) in the same household were found likely to be tested positive for CHIKV antibodies. Conclusions: Findings from the study support that asymptomatic CHIKV infections and indoor transmission occurred during the outbreak. Hence, widespread community testing and indoor use of mosquito repellent are among the possible measures that can be implemented to reduce CHIKV transmission during an outbreak.